A new pattern of dendrobranch gill within the family Solenoceridae (Crustacea: Decapoda: Dendrobranchiata) - Tavares, Carolina; Serejo, Cristiana (Zootaxa, 2019)
Mostly, gills are simple lamellate structures, but in decapods they can assume three elaborate morphologies: trichobranchiate, phyllobranchiate and dendrobranchiate. The dendrobranchiate gill, typically found among the suborder Dendrobranchiata, primarily consists of a long central axis, from which arises a series of paired secondary branches. Each secondary branch is subdivided into smaller fingerlike tertiary processes, and each fingerlike process is also branched (dendritic). The family Solenoceridae is known for having the dendrobranchiate type. Examen of 50 species of Solenoceridae from all nine genera, revealed a new pattern to the classic dendrobranchiate type in 14 species of Solenocera and in Mesopenaeus tropicalis. This new pattern consists of the flattening of the secondary and tertiary processes, with tertiary processes also having a wide, flattened, lamella-like base. This new pattern is herein described as a dendrolamellate gill.